Chronologia i metryka rozwoju ontogenetycznego = Chronology and metrics of ontogenetic development - Karandašev, Yuri (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The central problem of development psychology, and psychology in general, is a way of dividing of life into periods called in European tradition as a periodization of ontogenesis. Nor just the division of life into separate periods, but the creation of a theory that would explain why the individual life is divided into periods in a certain way. Only with such a theory, it is possible to wonder about the age periods and the duration of their borders. The solution of second problem appears as an objective of this article.
Keywords: ontogeneza; chronologia ontogenezy; metryka ontogenezy; periodyzacja rozwoju; poziomowa periodyzacja ontogenezy; ewolucyjna koncepcja ontogenezy; ontogenesis; chronology of ontogenesis; metrics of ontogenesis; way of dividing of life into periods; periodization of ontogenesis; multi-level periodization of development; evolutionary theory of development